2018
DOI: 10.1097/sle.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laparoscopic and Open Pancreaticoduodenectomy for the Treatment of Nonpancreatic Periampullary Adenocarcinomas

Abstract: Background:Laparoscopic pancreaticoduodenectomy (LPD), a surgical option for nonpancreatic periampullary adenocarcinoma (NPPA), is a complex procedure that has become increasing popular. However, there is no consensus as to whether this technique should be performed routinely. Our aim was to evaluate the outcomes of LPD compared with open pancreaticoduodenectomy (OPD).Materials and Methods:From October 2010 to September 2015, 58 LPDs were performed to treat NPPA and were compared with 58 OPDs, which can theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 24 publications
3
39
1
1
Order By: Relevance
“…Another two publications were then excluded due to overlapping patient cohorts [ 12 , 13 ]. Finally, a total of 9443 patients [LPD 1196 (12.7%), OPD 8247 (87.3%)] from 11 studies were included [ 14 24 ]. Figure 1 illustrates the selection process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another two publications were then excluded due to overlapping patient cohorts [ 12 , 13 ]. Finally, a total of 9443 patients [LPD 1196 (12.7%), OPD 8247 (87.3%)] from 11 studies were included [ 14 24 ]. Figure 1 illustrates the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Only one RCR was found [ 22 ]. The indication of six studies was PDAC [ 14 , 16 20 ], whereas two studies applied LPD only to PAAC [ 15 , 24 ], the remaining three researches reported both PDAC and PAAC [ 21 23 ]. Table 1 lists the characteristics of these studies and details of the enrolled participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that laparoscopic pancreaticoduodenectomy is better than open pancreaticoduodenectomy. [14] However, some studies reported that laparoscopic pancreaticoduodenectomy is a difficult procedure associated with a high morbidity. They concluded that laparoscopic pancreaticoduodenectomy should not be used routinely for resection of periampullary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that laparoscopic pancreaticoduodenectomy should not be used routinely for resection of periampullary tumors. [14] Meng et al [14] reported that laparoscopic pancreaticoduodenectomy is a feasible, effective and safe method for the treatment of nonpancreatic periampullary adenocarcinoma which may be used as an alternative to open pancreaticoduodenectomy. In our study, dissection was easier in a patient with an ampullary tumor.…”
Section: Discussionmentioning
confidence: 99%